2006
DOI: 10.1051/0004-6361:20054172
|View full text |Cite
|
Sign up to set email alerts
|

X-ray flare in XRF 050406: evidence for prolonged engine activity

Abstract: We present observations of XRF 050406, the first burst detected by Swift showing a flare in its X-ray light curve. During this flare, which peaks at t peak ∼ 210 s after the BAT trigger, a flux variation of δF/F ∼ 6 in a very short time δt/t peak 1 was observed. Its measured fluence in the 0.2−10 keV band was ∼1.4 × 10 −8 erg cm −2 , which corresponds to 1−15% of the prompt fluence. We present indications of spectral variations during the flare. We argue that the producing mechanism is late internal shocks, wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
78
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 58 publications
(75 reference statements)
6
78
0
Order By: Relevance
“…Our results ( Fig. 1 and Table 1) suggest that usually the t 0 values are near the beginning of the rising segment of the last pulse of the prompt emission or the corresponding X-ray flare, which is consistent with the expectation of the internal dissipation models for the prompt emission and X-ray flares (e.g., Burrows et al 2005;Zhang et al 2006a;Fan & Wei 2005;Ioka et al 2005;Falcone et al 2006;Romano et al 2006). This suggests that the GRB central engine reactivates after the early prompt emission is over, sometimes up to days after the trigger (e.g., GRB 050502B and GRB 050724).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results ( Fig. 1 and Table 1) suggest that usually the t 0 values are near the beginning of the rising segment of the last pulse of the prompt emission or the corresponding X-ray flare, which is consistent with the expectation of the internal dissipation models for the prompt emission and X-ray flares (e.g., Burrows et al 2005;Zhang et al 2006a;Fan & Wei 2005;Ioka et al 2005;Falcone et al 2006;Romano et al 2006). This suggests that the GRB central engine reactivates after the early prompt emission is over, sometimes up to days after the trigger (e.g., GRB 050502B and GRB 050724).…”
Section: Conclusion and Discussionsupporting
confidence: 89%
“…Zhang et al (2006a) performed more detailed analysis of various possible scenarios and concluded that the late internal dissipation model is the correct interpretation of X-ray flares. Similar conclusions have been also drawn by Ioka et al (2005), Fan & Wei (2005), Falcone et al (2006), and Romano et al (2006) (see Piro et al 2005; C. D. Dermer 2006, in preparation).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…Quite often an erratic flaring behaviour is observed superimposed on these phases Falcone et al 2006;Romano et al 2006). The most accredited explanation for the steep phase is that we are seeing high-latitude emission due to the termination of the central engine activity (Kumar & Panaitescu 2000;Zhang et al 2006), while flares are probably due to the reactivation of the central engine.…”
Section: Discussionmentioning
confidence: 96%
“…This has become a general feature of both long and short GRBs in view of the commonly detected X-ray flares hundreds of seconds after the burst trigger, which are generally interpreted as late central engine activities Zhang et al 2006;Romano et al 2006;Falcone et al 2006;Barthelmy et al 2005b;Campana et al 2006;Liang et al 2006). The second main peak (excluding the precursor) would have been categorized as an X-ray flare had it been even softer.…”
Section: Fig 12mentioning
confidence: 99%